REVIEW CONSENSUS EFFECTS ON E-WOM AND CONSUMER GOODS E- PURCHASE SATISFACTION: A QUANTITATIVE INVESTIGATION.. - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (The journal of contemporary issues in business and government, 2022)
E-WOM refers to ''''''''Electronic Word of Mouth,'''''''' which works to gather the reviews of the consumers who are buying and shopping goods online. In the last decade, there has been a surge in online shopping and the e-purchase of various goods and products. Review consensus gives a source of trust and faith for the online buyer who is buying a product by seeing its images without any physical interaction or communication with the seller. Fewer and less comprehensive reviews systems fail to give the online buyer and consumer an accurate product picture. Therefore, an extensive collection of detailed and informative reviews is needed to sell most online products. In the present day, there are 328 online buyers of goods and services, which is rapidly increasing each day. So, the importance of Review Consensus on e-WOM and consumer goods e-purchase satisfaction is paramount. One hundred twenty-nine respondents were collected through a "standard questionnaire" created on a five-point interval scale.